Protecting my injured child: a qualitative study of parents’ experience of caring for a child with a displaced distal radius fracture - Phelps, E; Tutton, E; Costa, M; Achten, J; Moscrop, A; Perry, D (BioMed Central, 2022)
Background: Childhood fractures can have a significant impact on the daily lives of families affecting children’s normal activities and parent’s work. Wrist fractures are the most common childhood fracture. The more serious wrist fractures, that can look visibly bent, are often treated with surgery to realign the bones; but this may not be necessary as bent bones straighten in growing children. The children’s radius acute fracture fixation trial (CRAFFT) is a multicentre randomised trial of surgery versus a cast without surgery for displaced wrist fractures. Little is known about how families experience these wrist fractures and how they manage treatment uncertainty. This study aimed to understand families’ experience of this injury and what it is like to be asked to include their child in a clinical trial.